Implementation of Project-Based Learning Model to Improve Creative Thinking of Elementary School Teacher Education Students in Social Sciences Learning in Upper-Level Class Course - Supriatna, Encep; Fitriani, Yulianti; Ali, Ismail; Hotìmah, Iis Husnul (Universitas Pendidikan Indonesia Kampus Serang, 2024)
The Indonesian authority encourages that higher education institutions should carried out in a non-lecturing manner, in the form of a case method and team-based project. Therefore, the Universitas Pendidikan Indonesia requires all lecturers to create collaborative and participatory classes. The Social Sciences Learning in the Upper-Level Class Course used the project-based learning (PjBL) model in the form of visits to museums and making videos of the results of their visits, so it is important to investigate the implementation and results of the practice to enhance critical thinking. The subjects of this qualitative study were fourth-semester students at the UPI Serang Campus Elementary School Teacher Education Study Program. The method employed in this research was a descriptive qualitative using observation and questionnaire data collection. The data analysis used the Miles and Huberman framework, comprising data reduction, data display, verification, and conclusion. The results of the research demonstrated that the application of the PjBL model in the course by creating videos and YouTube platforms revealed that students' creativity increased because they were given the freedom to explore their creative thinking in carrying out the project. This is shown by the percentage of 27.21% was in very students completing assignments, with excellent criteria and the rest gained good criteria according to the rubric given. The implementation could be the best practice of PjBL in higher education to increase student creative thinking